Structural, Electronic, and Mechanical Properties of Inner Surface Modified Imogolite Nanotubes - da Silva, Maurício Chagas; dos Santos, Egon Campos; Lourenço, Maicon Pierre; Gouvea, Mateus Pereira; Duarte, Hélio Anderson (Frontiers in Materials, 2015)
The electronic, structural and mechanical properties of the modified imogolites have been investigated using self consistent charge-density functional-tight binding method with “a posteriori” treatment of the dispersion interaction (SCC-DFTB-D). The zigzag (12,0) imogolite has been used as the initial structure for the calculations. The functionalization of the interior (12,0) imogolite nanotubes by organosilanes and by heat treatment leading to the dehydroxylation of the silanols were investigated. The reaction of the silanols with the trimethylmethoxysilanes is favored and the arrangement of the different substitutions that leads to the most symmetrical structures are preferred. The Young moduli and band gaps are slightly decreased. However, the dehydroxylation of the silanol groups in the inner surface of the imogolite leads to the increase of the Young moduli and a drastic decrease of the band gap of about 4.4 eV. It has been shown that the degree of the dehydroxylation can be controlled by heat treatment and tune the band gap, eventually, leading to a semiconductor material with well defined nanotube structure.